Effect of Citric Acid on Electrochemical Properties of Liquid Electrolytes - Noor, Nur Farah Izzati Mohd; Saidin, Saiyidah Nafisah; Raâ€™il, Nur Hani; Mobarak, Nadhratun Naiim (Jurnal Ilmu Fisika, 2021)
Effect of citric acid as plasticizer on the electrochemical properties of liquid electrolyte has been studied. Liquid electrolyte was prepared by dissolving citric acid in 1% acetic acid with presence of lithium nitrate salt. Liquid electrolyte is characterized using a conductivity meter to measure the ionic conductivity value. Computer simulation of Density Functional Theory (DFT) with B3LYP/6-31G ++ (d, p) basic set was performed to identify the dominant functional group of citric acid when interact with lithium salt. Increasing the weight of citric acid has increased the ionic conductivity up to 44.89 mS/cm with an optimum weight of 4 g, while the ionic conductivity increases up to 43.00 mS/cm when the percentage of lithium nitrate salt increases up to 30%. The ionic conductivity increases as the salt percentage increases due the interaction between salt and functional group of citric acid. Based on computer simulation of DFT, Â the dominant functional group in citric acid that interact with lithium salt are carboxylic acid group which is located in the middle of the citric acid chain causing lithium ions to be more likely interact with citric acid.